A study on maternal and perinatal out comes in cases of eclampsia admitting to government medical college and general hospital, Anantapuramu, Andhra Pradesh, India - Shaikh, Shamshad Begum; Jampala, Sandhya; S., Shyamala Devi; ., Mallika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Eclampsia is a life threatening emergency that continues to be a major risk factor dictating the outcome of pregnancy and is still the leading etiological factor of maternal mortality worldwide. The aim was to study the incidence of eclampsia at Government General Hospital, Anantapuramu, Andhra Pradesh, India, to evaluate the clinical course and complications and to study the maternal and perinatal outcome in eclamptic patients. Methods: Current study is a retrospective study carried out based on the data acquired from the case records of all eclampsia patients who admitted in the department of obstetrics and gynecology, government general hospital, Anantapuramu, Andhra Pradesh, India from February 2015 to February 2016. Data was recorded in a pretested proforma and was analyzed using appropriate statistical methods. Results: Out of a total of 8595 deliveries conducted during the study period, 50 cases of eclampsia were recorded making the incidence of eclampsia to be 0.58% in the hospital. There were no maternal deaths occurred during the study period. Total numbers of perinatal deaths due to eclampsia were 14, hence the perinatal mortality rate for eclampsia was 280/1000. Majority of the patients were unbooked (90%). 78% of patients were primigravidas and 80% of patients were less than 25 years of age. Antepartum eclampsia was seen in 72% of the cases, intrapartum eclampsia in 4% patients and postpartum eclampsia was found in 24% of the patients. Vaginal delivery was a common mode of delivery conducted in 56% of patients while 44% of the patients required caesarean section. Conclusions: Eclampsia continues to be an important etiological factor for maternal/perinatal morbidity and mortality. The contributory factors for this being lack of proper antenatal care, low socio economic status and lack of education. There is an urgent need for proper antenatal care, proper medication (magnesium sulfate), intensive monitoring of women with eclampsia and timely hospitalization to improve both the maternal and perinatal outcome. Early presentation and timely decision to terminate pregnancy will improve the maternal and perinatal outcome.